Social Media as a Medium of Da’wah: Religious Transformation among Online Da’wah Audience on TikTok Platform - Fitri Maghfirah; Fitria Andriani; Husnul Mirzal (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
This study aims to examine the da’wah activities movement in the Tik Tok application, and the religious transformation that is felt by listeners of Da’wa in the Tik Tok application. This study used a qualitative method with a phenomenological approach. Data collection was carried out through interview techniques, observation, questionnaire distribution, and in-depth review of previous research literature. The results of this study indicate that the Tik Tok media has been colored by creative Islamic da’wah video content so that it can attract a lot of attention from Tik Tok users, as well as being a breakthrough to eliminate negative justifications that are often pinned generally on Tik Tok . The creativity carried out by Da’wa Tik Tokers can be classified as a modern reconstruction of da’wah, so that the message conveyed seems more relaxed and in accordance with the times. Meanwhile, with the presence of da’wah content on Tik Tok, listeners have experienced several religious transformations, such as getting closer to Allah, avoiding bad deeds, gaining mental peace, and increasing spiritual values. The religious transformation experienced by listeners of Da’wa on Tik Tok is not only caused by the da’wah content on Tik Tok but may also be caused by other external factors. The results of this research are expected to be useful as an inspiration to da’wah activists to try to do da’wah activities in creative and innovative ways, one of which is through the Tik Tok application. In addition, this research is expected to be able to add literature in the field of Islamic studies, especially in the field of da’wah. Keywords: Da’wah, religious transformation, and Tik Tok.